"Orędownicy kolektywizacji" na podstawie księgozbioru biblioteki w osadzie wiejskiej Czerwieńsk w powiecie zielonogórskim w latach 1949-1956 = Advocates of collective farming based on the book collection in the rural settlement?s library in Czerwieńsk, Zielona Góra District between 1949-1956 - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1948 Polish communists initiated a socialist redevelopment of a village based on Soviet experience. The purpose of this process was to locate farmers in production cooperatives which were controlled by the country. This operation was also supported by librarians, who in the rural settlement of Czerwieńsk, Zielona Gora District, between 1949-1956 offered books which would encourage peasants to support the idea.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia